Exploring the Influence of Storytelling Activities on the Development of Literacy of Children Aged 5-6 Ye - Bunayyah, Siti; Setyowati, Sri; Malaikosa, Yes Matheos Lasarus; Adhe, Kartika Rinakit; Kristanto, Andi; Fitri, Ruqoyyah (Papanda Publisher, 2025)
This qualitative research explores the impact of storytelling activities on early literacy development among children aged 5–6 years at TK Islam Al Baqy, Gresik. Storytelling, as an interactive pedagogical tool, is increasingly recognized for its potential to foster foundational literacy skills in early childhood education. The study aimed to examine how structured storytelling sessions contribute to children’s listening, vocabulary, verbal expression, and comprehension abilities. Data were collected through classroom observations and semi-structured interviews with teachers and parents, and were analyzed thematically. The study involved 20 children and 4 teachers as participants. Findings indicate that storytelling significantly enhanced children's attentiveness, language confidence, and narrative thinking. Children engaged actively during storytelling sessions and demonstrated improved ability to retell stories, respond verbally, and use newly introduced vocabulary in daily communication. Moreover, storytelling facilitated socio-emotional development by nurturing empathy, imagination, and cooperative interaction among peers. Teachers reported that students became more motivated and expressive in classroom activities after consistent exposure to storytelling. The study concludes that storytelling is an effective, accessible, and developmentally appropriate method for promoting literacy in early learners. Despite its limited scope—focused on one school and a short observation period—this research provides empirical insights into the pedagogical integration of storytelling. It recommends wider adoption of storytelling in early childhood curricula and further investigation into its long-term effects. This study contributes to the growing body of knowledge on narrative-based learning and reinforces storytelling’s role as a vital strategy for fostering early literacy and holistic development in young children.